Improvement of Dissolution Characteristics of Edoxaban through Solid Dispersion Technique (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: This study aimed to identify the most effective carrier system for enhancing the solubility of Edoxaban(EDO) through the preparation of solid dispersions (SDs) using a novel microwave-induced fusiontechnique. Materials and Methods: Various carriers including PEGs (3350–20000), PVPs (K-12–K-90),Poloxamers (108–407), and urea were employed to prepare SDs of EDO. Drug–carrier compatibility wasassessed, followed by evaluation of SD flow properties. SDs were compressed into tablets and analyzedfor physicochemical parameters such as thickness, hardness, friability, drug content, solubility, and invitro dissolution. A high-performance liquid chromatography method was developed to quantify drugrelease. Results: Among all carriers, a blend of PEG-8000, PVP-K-30, and Poloxamer 188 showed the bestenhancement in EDO solubility and dissolution rate. The optimized formulation exhibited superior physicaltablet properties and content uniformity. Accelerated stability studies confirmed formulation robustness.In vivo release studies and pharmacokinetic comparisons with a marketed product confirmed enhancedbioavailability. Conclusion: The combination of PEG-8000, PVP-K-30, and Poloxamer 188 in microwaveinducedSDs significantly improved the solubility and performance of EDO, demonstrating a promisingstrategy for enhancing poorly soluble drugs.